Biochemical Approaches on Commercial Strains of Agaricus subrufescens Growing under Two Environmental Cultivation Conditions - Daiana Almeida; Rossana V. C. Cardoso; Carla Pereira; Maria José Alves; Isabel C. F. R. Ferreira; Diego Cunha Zied; Wagner G. Vieira Junior; Cinthia E. C. Caitano; Ângela Fernandes; Lillian Barros (Journal of Fungi, 2022)
In the present work, the effect of the cultivation process, in the field and under a controlled environment, on biochemical parameters by using commercial strains of A. subrufescens were evaluated. The results obtained revealed that the strains cultivated in the field presented higher levels for most of the parameters evaluated (organic acids (20.5–48.0 g/100 g dw), tocopherols (107.0–198.6 µg/100 g dw), and phenolic acids and related compounds (245.2–359.0 µg/100 g dw and 10.6–23.7 µg/100 g dw, respectively)), except for the carbohydrates (53.4–72.6 g/100 g dw), energetic value (373–380 Kcal/100 g dw), and total free sugars (28.8–43.1 g/100 g dw), parameters in which the strains grown in a controlled environment present better results. For both cultivation systems, similar results were obtained regarding saturated, monounsaturated, and polyunsaturated fatty acids, as well as antioxidant and antimicrobial activities. These data contribute to the knowledge and highlight the characterized strains and the cultivation process, which can be used to obtain ingredients with potential applicability as a source of functional compounds.